Frequency-dependent retinal responsiveness to sinusoidal electrical stimulation in achromatopsia. (January 2023) - Jung, Ronja; Kempf, Melanie; Pohl, Lisa; Kortüm, Friederike; Reith, Milda; Kelbsch, Carina; Kohl, Susanne; Wilhelm, Helmut; Wilhelm, Barbara; Stingl, Katarina; Stingl, Krunoslav
Abstract: Recently, we proposed a method to assess cell-specific retinal functions based on the frequency-dependent responses to sinusoidal transcorneal electrostimulation. In this study, we evaluated the alterations in responsiveness in achromatopsia patients to explore the frequency-selectivity of photoreceptors. The electrical stimulation was applied to one eye of genetically confirmed achromatopsia patients via corneal electrodes. The stimulus was composed of amplitude-modulated sine waves with variable carrier frequencies (4–30 Hz) and a steady low-frequency envelope. The retinal responsiveness across the spectrum was calculated based on the velocity and the synchronicity of the electrically evoked pupillary oscillations. Achromats displayed a characteristic peak in responsiveness in the 6–10 Hz range. In contrast, stimulus frequencies above 16 Hz elicited only weak pupil responses and weak phosphenes. Compared to the tuning curve of the healthy retina, responses to low-frequency stimulation appear to reflect mainly rod activation while higher frequencies seem to activate cones. The possibility to examine cell-specific retinal functions independently from their responses to light may improve our understanding of the structural changes in the retina induced by gene therapy. Highlights: We assessed the retinal responsiveness to electrical stimuli (4–30 Hz) in Achromats. Pupillary responses and phosphenes served as read-outs for the responsiveness. Low frequencies usually elicited strong (normal to hyper-normal) responses. High frequencies (above 14 Hz) evoked no phosphenes and weak pupillary responses. These results suggest that rods selectively respond to low-frequency stimulation.